2015
DOI: 10.1093/bioinformatics/btv555
|View full text |Cite
|
Sign up to set email alerts
|

Identification of coupling DNA motif pairs on long-range chromatin interactions in human K562 cells

Abstract: Motivation: The protein-DNA interactions between transcription factors (TFs) and transcription factor binding sites (TFBSs, also known as DNA motifs) are critical activities in gene transcription. The identification of the DNA motifs is a vital task for downstream analysis. Unfortunately, the longrange coupling information between different DNA motifs is still lacking. To fill the void, as the first-of-its-kind study, we have identified the coupling DNA motif pairs on long-range chromatin interactions in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Recent studies identifying the co-occurrence of TF pairs focus either on combinatorial approaches where e.g., specific DNA-sequences bound by different TFs simultaneously were selected from a library of random sequences (Jolma et al, 2015 ) or approaches that focus on data integration e.g., ChIP-seq, SELEX together with Hi-C to reveal long-range chromatin interactions (Jolma et al, 2013 ; Wong et al, 2016 ). Although the selection of interacting TF pairs from a library of random sequences underpins potential interactions of TFs, it does not give any hints on the actual interactions in particular cell types or tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies identifying the co-occurrence of TF pairs focus either on combinatorial approaches where e.g., specific DNA-sequences bound by different TFs simultaneously were selected from a library of random sequences (Jolma et al, 2015 ) or approaches that focus on data integration e.g., ChIP-seq, SELEX together with Hi-C to reveal long-range chromatin interactions (Jolma et al, 2013 ; Wong et al, 2016 ). Although the selection of interacting TF pairs from a library of random sequences underpins potential interactions of TFs, it does not give any hints on the actual interactions in particular cell types or tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is RNA splicing, a biological process in which sequences have sub-sequences removed and concatenated [Ule and Blencowe, 2019] (e.g., to convert the word "machine" to "m...ine" to "mine"). Here, fuzzy motifs also cooperate in a distance-dependent fashion, potentially involving very long-range interactions [Wong et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies pointed out a new venue to explore the characteristics of EP interactions, which suggested that the interaction of transcription factors (TFs) that bind an enhancer and TFs that bind a promoter of an EP pair may contribute to the interaction of this EP pair [2,12,20,[26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%